Effect of intense pulsed light on immature burn scars: A clinical study - Arindam Sarkar; Yatindra Kumar Dewangan; Jayanta Bain; Pritha Rakshit; Krishnanand Dhruw; Sandip Kanti Basu; Jayanta Kumar Saha; Bijay Kumar Majumdar (Indian Journal of Plastic Surgery)
Introduction: As intense pulsed light (IPL) is widely used to treat cutaneous vascular malformations and also used as non-ablative skin rejunuvation to remodel the skin collagen. A study has been undertaken to gauze the effect of IPL on immature burn scars with regard to vascularity, pliability and height. Materials and Methods: This study was conducted between June 2013 and May 2014, among patients with immature burn scars that healed conservatively within 2 months. Photographic evidence of appearance of scars and grading and rating was done with Vancouver Scar Scale parameters. Ratings were done for both case and control scar after the completion of four IPL treatment sessions and were compared. Results: Out of the 19 cases, vascularity, pliability and height improved significantly (P < 0.05) in 13, 14 and 11 scars respectively following IPL treatment. Conclusions: Intense pulsed light was well-tolerated by patients, caused good improvement in terms of vascularity, pliability, and height of immature burn scar.